STOCK MARKET INDICATORS AND ECONOMIC GROWTH: A CAUSALITY TEST FOR NIGERIA - Ugwuanyi, Charles Uche; Ukwueze, Alphonsus O. (EBSU Journal of Social Sciences and Humanities, 2022)
The empirical relationship between stock market indicators and economic growth was tested in this paper by employing the Granger-causality test, co-integration test and vector Auto Regression analysis in the series used. It was found that causality runs from value of transaction to output and there is bi-directional causality between total market capitalisation and output. The result of the cointegration revealed two (2) co-integration equations. This suggests that there is long-run relationship among the variables. The VAR result equally, suggests close relationship between the stock market indicators and economic growth in Nigeria. It shows that stock market positively and significantly influences economic growth in Nigeria. The results suggest effective co-ordination of legal, regulatory and administrative systems of the stock market. The findings, equally suggest efficient and effective co-ordination of monetary and fiscal policies that encourage investors confidence and stock liquidity.